Personal development in counsellor training - Johns, Hazel (Counsellor trainer and supervisor series, 2012)
Provides the answers to the important question: what is personal and professional development and why is it necessary for counsellors? Packed full of accounts of personal experiences, questions and points for refection, this book will prove an essential companion for anyone wishing to grow personally and professionally as a therapist